2021
DOI: 10.3390/min11080886
|View full text |Cite
|
Sign up to set email alerts
|

Research on Strength Prediction Model and Microscopic Analysis of Mechanical Characteristics of Cemented Tailings Backfill under Fractal Theory

Abstract: In order to further study the internal relationship between the microscopic pore characteristics and macroscopic mechanical properties of cemented tailings backfill (CTB), in this study, mine tailings and ordinary Portland cement (PC32.5) were selected as aggregate and cementing materials, respectively, and different additives (anionic polyacrylamide (APAM), lime and fly ash) were added to backfill samples with mass concentration of 74% and cement–sand ratios of 1:4, 1:6 and 1:8. After 28 days of curing, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, there is a lack of research results on the use of acoustic emission and ultrasonic signal characteristics to monitor and warn about the deformation damage of LCTB. Therefore, this paper performs uniaxial compression acoustic emission tests and ultrasonic tests on LCTB based on previous studies on the mechanical properties of LCTB [18][19][20][21] and the acoustic emission and ultrasonic characteristics of intact cemented tailings backfill [22][23][24][25]. Two factors-different filling times and filling interval time-are considered to analyze the changes in acoustic emission and ultrasonic signals during the deformation and damage of LCTB.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of research results on the use of acoustic emission and ultrasonic signal characteristics to monitor and warn about the deformation damage of LCTB. Therefore, this paper performs uniaxial compression acoustic emission tests and ultrasonic tests on LCTB based on previous studies on the mechanical properties of LCTB [18][19][20][21] and the acoustic emission and ultrasonic characteristics of intact cemented tailings backfill [22][23][24][25]. Two factors-different filling times and filling interval time-are considered to analyze the changes in acoustic emission and ultrasonic signals during the deformation and damage of LCTB.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have carried out a series of studies on the internal relationship between micro-pore structure and mechanical properties. Many researchers [ 16 , 17 , 18 ] have used different detection methods to explore the micro-pore structure. Zhang [ 19 ], Deng [ 20 ], Li [ 21 , 22 , 23 , 24 ] discussed the evolution of the micro-pore structure of sandstone and granite samples under freeze-thaw cycles through NMR, establishing the relationship between porosity and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of research, it has been found that the nature of the decrease in mechanical properties of freezing-thawing porous materials is that the freezing-thawing action changes their internal microstructure [25][26][27][28][29][30][31][32][33][34]. Tang, LY [35] used nuclear magnetic resonance (NMR) to analyze the effect of freeze-thaw cycles on the internal pore structure of the soil-rock mixture.…”
Section: Introductionmentioning
confidence: 99%